PENGARUH KEPEMILIKAN INSTITUSIONAL, KEPEMILIKAN MANAJERIAL TERHADAP NILAI PERUSAHAAN DAN DAMPAKNYA TERHADAP COST OF EQUITY CAPITAL. (Studi Pada Emiten Manufaktur Di Bursa Efek Indonesia) - Elviza - (Jurnal Akuntansi Muhammadiyah (JAM), 2010)
The purpose of this study was to examine and analyze the influence of institutional ownership and managerial ownership on firm value and its impact on the cost of equity capital either partially or simultaneously at the Stock Exchange listed companies manufacturing in Indonesia. This type of research is verification research with census method.The population of this study is that all manufacturing companies in Indonesia Stock Exchange that owns shares of managerial and institutional. Having selected the target population totaled 59 issuers. The analytical method used was path analysis (path analysis). Data used in this research is secondary data, obtained from audited financial statements for the fiscal year ended December 31, 2005 and as of December 31, 2008, and the stock price data during the observation period, issued by manufacturing companies and published by the Reference Center Capital Markets (PRPM) found on the Indonesian Stock Exchange (BEI).The results of this study indicate that, (1) institutional ownership and managerial ownership simultaneously affect firm value, (2) institutional ownership, managerial ownership and firm value simultaneously affect the cost of equity capital (3) Institutional Ownership partially give effect weak value of the firm (4) Managerial ownership partially provide a weak effect on the value of the firm (5) Institutional Ownership partially affect the cost of equity capital (6) Managerial ownership partially affect the cost of equity capital (7) value company partially affect the cost of equity capital. Keywords: institutional ownership, managerial ownership, corporate value and   cost of equity capital.